Molecular evolution of nitric oxide synthases in metazoans. - Muñoz-Chápuli-Oriol, Ramón; González-Doménech, Carmen María (My University, 2010)
Nitric oxide synthases (NOS), the enzymes responsible for the NO synthesis, are present in all eukaryotes. Three isoforms (neuronal, inducible and endothelial), encoded by different loci, have been described in vertebrates, although the endothelial isoform seems to be restricted to tetrapods. In invertebrates, a variety of NOS isoforms have been variably annotated as "inducible" or "neuronal", while others lack precise annotation. We have performed an exhaustive collection of the available NOS amino-acid sequences in order to perform a phylogenetic analysis. We hypothesized that the NOS isoforms reported in vertebrates derive from 1) different invertebrate NOS, 2) a single invertebrate ancestral gene, through an event related to the double whole genomic duplication that occurred at the origin of vertebrates, and 3) the endothelial form of NOS appeared late in the evolution of vertebrates, after the split of tetrapods and fishes. Our molecular evolution analysis strongly supports the second scenario, the three vertebrate NOS isoforms derived from a single ancestral invertebrate gene. Thus, the diverse NOS isoforms in invertebrates can be explained by events of gene duplication, but their characterization as "inducible" or "neuronal" should only be justified by physiological features, since they are evolutionarily unrelated to the homonym isoforms of vertebrates.
Keywords: Evolución química; Oxido nítrico; Metazoos; Molecular evolution; Nitric oxide synthases; Metazoans